An analysis of The Halal Certification Movement for MSME (Micro, Small, and Medium Enterprises) Actors: A Case Study on Halal Tourism in Kudus Regency - Nafis, Abdul Alimin; Agung Slamet Sukardi; Muhammedi, Ssonko (Universitas Muhammadiyah Surakarta, 2024)
Kudus Regency is one of the districts that has tourism potential in the field of halal tourism, where elements that support halal tourism include MSMEs, even though halal certification on MSME products is still minimally applied by MSME actors, especially those in halal tourism in Kudus Regency. The lack of knowledge is also one of the reasons why MSME actors and administrative procedures need to be better understood by MSME actors. This study aims to provide an understanding of the urgency of the halal certification movement for MSME actors in the halal tourism sector so that it is expected to create new jobs. This research uses a qualitative approach by interviewing ten people consisting of MSME actors, where the interview emphasizes the importance and understanding of Halal certification in MSMEs. The results of this study show that with Halal certification on MSME products, consumers increasingly trust and get guarantees from these products, so products that have Halal certification increasingly show that they are worthy of a massive market. The government, Halal Certification Companions, and stakeholders are advised to play a vital role in enhancing MSME participants' understanding of halal certificates for MSME products in halal tourism zones, according to this study.